Discussion: Problems Confronting Bulgarian Higher Education - Kozhuharov, Hristo (Research Papers, 2007)
There are specified the problems of the education connected with the necessity of accepting a conception and developing a strategy for the education reform at the time of keeping the national culture. There are also considered questions that are having an attitude the higher education in our country: contents of school syllabuses and programs, self-dependent student’s work and student motivation, crediting, the mobile in the education, methods of examination etc. It is attended to the quality of the education and to the part of the lecturer in the school process, to his research work, scientific rising and attestation and to the payment for his work. It is considered, on the basis of the current problems, the necessity of accepting a new low of the higher education.